Edrophonium challenge test for blepharospasm - Matsumoto, Shinichi; Murakami, Hisanaga; Koizumi, Hidetaka; Takahashi, Masatoshi; Izumi, Yuishin; Kaji, Ryuji (Frontiers in Neuroscience, 2016)
Background: Blepharospasm is typically diagnosed by excluding any secondary diseases and neuropsychiatric disorders, as specific tests for blepharospasm are currently unavailable. Since anticholinergic agents are used to improve the symptoms of dystonia, we hypothesized that edrophonium chloride, an acetylcholinesterase inhibitor, may make the symptoms of dystonia more apparent. Therefore, we examined whether an edrophonium challenge test would be useful for diagnosing blepharospasm. Methods: We studied 10 patients with blepharospasm and 10 with hemifacial spasms (as disease controls). We administered edrophonium and saline in this double-blind study. Before and after the injection, we recorded the clinical signs using a video camera to assess the objective symptoms every 2 min. Ten minutes after the isotonic sodium chloride and edrophonium injections, the patients evaluated their subjective signs using a visual analog scale (VAS). The objective signs on the video recordings were scored by specialists who were blind to the treatment. Results: The subjective and objective signs of the patients with blepharospasm were amplified by edrophonium. In contrast, the signs in patients with hemifacial spasms were not changed by the edrophonium challenge test. Conclusions: The edrophonium challenge test may be used to diagnose blepharospasm. The study was registered with a ICMJE recognized registry, the UMIN-CTR, with the number UMIN000022557.